Effect of changes in the sports regulations on the fight of taekwondo female players on the example of Beijing Olympic Tournaments 2008 and London 2012 - Kruszewski, A.; Kuzmicki, S.; Podchul, A.; Kruszewski, M. (Journal of Combat Sports and Martial Arts, 2014)
The rapid development of the World`s Olympic Taekwondo began with the introduction of this discipline to the programme of the Olympic Games. In its Olympic form, taekwondo fight is based on the rivalry of two players in a direct challenge, mainly to strike a specific blow at an opponent. All over the world the most popular Taekwondo dyscipline is Kyourugi - sports fight. The main objective of undertaken studies was to determine the effect of changes in sports regulations of taekwondo on the range of technical activities used by female athletes. Material and methods. In the study it was analyzed a total of 48 fights (84 players) in two Olympic taekwondo tournaments: Beijing - 2008 and London - 2012. There were observed 6 fights in each weight category (-49 kg, -57 kg, -67kg, over 67kg), 24 fights in each tournament. It was used the method of secondary direct analysis. Results. It was observed an increase in number of technical activities taken in upper zone - olgul (attack on an opponent`s head) and a decrease in number of technical activities in lower zone - montong (attack on an opponent`s trunk). Conclusions. The changes in the sports regulations have changed the range of technical acctivities used by female athletes in attack and counterattack. The players more often realized actions in the counterattack. In both analyzed tournaments it was found that a greater number of technical activities were taken towards a trunk (zone montong) than towards a head (zone olgul). However, it should be noted the significant statistical increase of technical activities towards olgul between the tournament in Beijing and the tournament in London (p <0.05).